Change of ethanol and stress induced gastric mucosal damage with vitamin-E in rats - Abdurrahman KAPLAN; Sabri BATUN; Orhan YAZANEL; Levent ERDİNÇ and Fikri CANORUÇ (Turkish Journal of Gastroenterology, 2020)
-